Reducing Cytoplasmic Polyamine Oxidase Activity in Arabidopsis Increases Salt and Drought Tolerance by Reducing Reactive Oxygen Species Production and Increasing Defense Gene Expression - Sagor, G. H. M.; Zhang, Siyuan; Kojima, Seiji; Simm, Stefan; Berberich, Thomas; Kusano, Tomonobu (Frontiers in Plant Science, 2016)
The link between polyamine oxidases (PAOs), which function in polyamine catabolism, and stress responses remains elusive. Here, we address this issue using Arabidopsis pao mutants in which the expression of the five PAO genes is knocked-out or knocked-down. As the five single pao mutants and wild type (WT) showed similar response to salt stress, we tried to generate the mutants that have either the cytoplasmic PAO pathway (pao1 pao5) or the peroxisomal PAO pathway (pao2 pao3 pao4) silenced. However, the latter triple mutant was not obtained. Thus, in this study, we used two double mutants, pao1 pao5 and pao2 pao4. Of interest, pao1 pao5 mutant was NaCl- and drought-tolerant, whereas pao2 pao4 showed similar sensitivity to those stresses as WT. To reveal the underlying mechanism of salt tolerance, further analyses were performed. Na uptake of the mutant (pao1 pao5) decreased to 75% of WT. PAO activity of the mutant was reduced to 62% of WT. The content of reactive oxygen species (ROS) such as hydrogen peroxide, a reaction product of PAO action, and superoxide anion in the mutant became 81% and 72% of the levels in WT upon salt treatment. The mutant contained 2.8-fold higher thermospermine compared to WT. Moreover, the mutant induced the genes of salt overly sensitive-, abscisic acid (ABA)-dependent- and ABA-independent- pathways more strongly than WT upon salt treatment. The results suggest that the Arabidopsis plant silencing cytoplasmic PAOs shows salinity tolerance by reducing ROS production and strongly inducing subsets of stress-responsive genes under stress conditions.